Enhancing Indigenous Content in Arts Curricula Through Service Learning with Indigenous Communities. - Bartleet, Brydie-Leigh; Bennett, Dawn; Power, Anne; Marsh, Kathy; Sunderland, Naomi (Office for Learning and Teaching, 2014)
Final report from a project that aimed to demonstrate how collaborative partnerships between students and Indigenous communities can create Indigenous curriculum content in culturally appropriate ways. Using service learning as its pedagogical framework and performing arts as its disciplinary base, the project extended prior work in this field to communicate how these projects develop students' intercultural competencies, transform their understandings of Indigenous culture, and support Indigenous communities through cultural knowledge exchange.